A novel anti-reflux esophagogastric anastomosis in totally laparoscopic proximal gastrectomy: Hao’s esophagogastrostomy by fissure technique (HEFT) - Ze-Qin Wang; Wen-Liang Cui; Yan-Feng Zhu; Ming-Ye Ma; Jian Wang; Zi-Hao Wang; Ya-Ping Wang; Jun Hong; Han-Kun Hao (World Journal of Surgical Oncology)
Abstract Background For adenocarcinoma localized at the gastroesophageal junction and the upper third of the stomach, proximal gastrectomy (PG) is a commonly used surgical method that preserves gastric function. For reconstruction after PG, an effective anti-reflux technique is crucial. This study proposes a novel fundoplication and valvuloplasty esophagogastrostomy technique, named as Hao’s esophagogastrostomy by fissure technique (HEFT). Methods A retrospective analysis was conducted on the clinical data of 11 consecutive cases that underwent totally laparoscopic proximal gastrectomy with HEFT at Huashan Hospital, Fudan University from September 2021 to January 2024. The demographics and clinics pathologic profiles, preoperative details, and postoperative outcomes of the patients were analyzed. And the reflux conditions were evaluated 6 months after surgery by endoscopy. Results All 11 patients successfully underwent the totally laparoscopic surgery. The operative time was 190 (150, 240) minutes, including a reconstruction duration of 30 (25, 30) minutes. No Clavien-Dindo grade II or higher complications occurred postoperatively, and the hospital stay was 6 (5, 7) days. Endoscopic findings at 6 months postoperatively indicated 2 cases of LA grade A esophagitis. Among them, 1 patient experienced reflux symptoms after overeating, which improved after using proton pump inhibitor drugs. Notably, there were no occurrences of anastomotic stenosis. Conclusion HEFT presents a promising approach for anti-reflux reconstruction following proximal gastrectomy (PG), simplifying the surgical technique while maintaining favorable immediate clinical outcomes. However, given that this is a retrospective study, further research with larger-scale clinical trials and long-term follow-up is essential to validate its safety, efficacy, and long-term benefits.